The Palgrave Handbook of Affect Studies and Textual Criticism
XXIX, 883 p. 30 illus.
Keywords: This volume provides a comprehensive account of how scholarship on affect and scholarship on texts have come to inform one another over the past few decades. The result has been that explorations of how texts address, elicit, shape, and dramatize affect have become central to contemporary work in literary, film, and art criticism, as well as in critical theory, rhetoric, performance studies, and aesthetics. Guiding readers to the variety of topics, themes, interdisciplinary dialogues, and sub-disciplinary specialties that the study of interplay between affect and texts has either inaugurated or revitalized, the handbook showcases and engages the diversity of scholarly topics, approaches, and projects that thinking of affect in relation to texts and related media open up or enable. These include (but are not limited to) investigations of what attention to affect brings to established methods of studying texts—in terms of period, genre, cultural contexts, rhetoric, and individual authorship.